2023
DOI: 10.3390/en16145506
|View full text |Cite
|
Sign up to set email alerts
|

Energy Flexibility and towards Resilience in New and Old Residential Houses in Cold Climates: A Techno-Economic Analysis

Abstract: One of the main sectors that contribute to climate change is the buildings sector. While nearly zero-energy buildings are becoming a new norm in many countries in the world, research is advancing towards energy flexibility and resilience to reach energy efficiency and sustainability goals. Combining the energy flexibility and energy resilience concept is rare. In this article, we aim to investigate the effect of energy efficiency in a new single-family building on the energy flexibility potential and resilienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…This can also provide backup heating during power outages. This also requires further studies for optimal design and integration [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can also provide backup heating during power outages. This also requires further studies for optimal design and integration [52].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, usually in flexibility the objective can be operational (energy) cost saving, whereas in resilience, habitability condition is the objective. For instance, the study carried out in Finland showed that by using the energy flexibility capability of varying the indoor room set-point temperature by 1.5 • C based on the price, the energy cost can be reduced [52]. The economical benefit is an important part of energy flexibility decisions.…”
Section: ✓ ✗mentioning
confidence: 99%